Thai Identities as Scened in Twenty-first Century Contemporary Thai Media Art - Kumjim, Prapon (Journal of Urban Culture Research, 2018)
The context of this discussion is framed around the much anticipated 2018 opening of two major international contemporary art biennales to be hosted in Thailand for the very first time. First to open will be the Bangkok Art Biennale in October 2018 and Thailand Biennale at Krabi will follow in November 2018. Undoubtedly the international contemporary art biennale spotlight will bring crowds of multinational contemporary art enthusiasts to Thailand in 2018. But before we can begin to understand artworks by overseas artists we must first attempt to understand Thai identities within the scope of contemporary art. Therefore, twenty-first century contemporary media art practices will be discussed with examples from seven contemporary Thai media artists whom have been selected to elucidate the complex jigsaw-like and multifaceted transformations of Thai identities through recent history.